2006
DOI: 10.1261/rna.7228806
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and 3T3-L1 pre-adipocyte differentiation

Abstract: MicroRNAs (miRNAs) have been suggested to play important roles in cell proliferation, apoptosis, and differentiation. In this study, we examined miRNA expression profiles during 3T3-L1 pre-adipocyte differentiation. We constructed miRNA libraries from pre-and post-differentiated 3T3-L1 cells, and identified the expression of 77 previously reported miRNAs and 3 new miRNAs. Next, we investigated the expression levels of 102 miRNAs, including those identified in the libraries, during adipogenesis by Northern blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
168
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(181 citation statements)
references
References 26 publications
11
168
0
2
Order By: Relevance
“…Emerging evidence has indicated that miR-26b is associated with the development of obesity. Several studies have demonstrated this, including in abdominal subcutaneous adipose tissue where miR-26b was closely correlated with the number of infiltrating macrophages (14) and was upregulated during adipogenesis in mice (15). In our previous study, it was also demonstrated that miR-26b was differentially expressed during differentiation of human preadipocytes and was affected by a number of adipokines, including tumor necrosis factor-α (TNF-α), leptin and resistin (16).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Emerging evidence has indicated that miR-26b is associated with the development of obesity. Several studies have demonstrated this, including in abdominal subcutaneous adipose tissue where miR-26b was closely correlated with the number of infiltrating macrophages (14) and was upregulated during adipogenesis in mice (15). In our previous study, it was also demonstrated that miR-26b was differentially expressed during differentiation of human preadipocytes and was affected by a number of adipokines, including tumor necrosis factor-α (TNF-α), leptin and resistin (16).…”
Section: Discussionmentioning
confidence: 84%
“…Previously, Klöting et al (14) indicated that miR-26b is closely correlated with the number of infiltrating macrophages in abdominal subcutaneous (SC) adipose tissue. In addition, it appears that miR-26b is upregulated during adipogenesis in mice and humans (15,16). In our preliminary study, it was identified that miR-26b is increased during adipogenesis of human multipotent adipose-derived stem cells and preadipocytes screened from miRNA microarray experiments (unpublished data).…”
Section: Introductionmentioning
confidence: 83%
“…Because microRNAs (miRNAs) have been shown to be important in gene regulation, it is not surprising that they have been implicated in the development of obesity (Williams and Mitchell 2012). Therefore, the understanding of the regulatory Several miRNAs expression patterns have been profiled during adipocyte differentiation (Kajimoto et al 2006;Xie et al 2009;Ortega et al 2010), others have been linked to adipocyte phenotype, and other obesity parameters (Kajimoto et al 2006;Takanabe et al 2008;Klöting et al 2009;Xie et al 2009;Ortega et al 2010;Heneghan et al 2011;Keller et al 2011;Ortega et al 2013) (Figure 2). For example, miR-21 was strongly expressed in human adipose tissue and positively correlated with BMI (Keller et al 2011).…”
Section: Micrornasmentioning
confidence: 99%
“…These experiments have mostly involved cultured pre-adipocytes, which can be stimulated to differentiate into a phenotype resembling mature fat-storing adipocytes. Kajimito et al [47] found in 3T3-LI pre-adipocytes in culture, 80 different miRNAs are expressed and 21 individual miRNAs are differentially expressed in the course of pre-adipocyte differentiation (most of the changes taking place in the late stages of differentiation). However, inhibiting the function of individual miRNAs (including miR-143) did not alter the course of the preadipocyte differentiation, nor did these perturbations alter the mRNA levels of marker genes PPAR-gamma, A-FABP, or adiponectin.…”
Section: Mirna Regulation In Adipocytes In Culturementioning
confidence: 99%